A discourse analysis of figurative language used in English storytelling on BBC Learning English - Azmi, Dhila Nurul; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek; Lestari, Sri (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
This study aims to discover the kinds of figurative language used that describe the meaning of those figurative languages in English Storytelling on BBC learning English. This study uses a qualitative method with a descriptive analysis approach. For the data, the primary source of this study is Storytelling from BBC Learning English. Secondary sources include books, publications, journal articles, English encyclopedias, observations, and documentation relevant to the research. After analyzing the kinds of figurative language in Storytelling on BBC Learning English, the study found 15 sentences that involve figurative language in English storytelling. There are four kinds of figurative language: personification, metaphor, hyperbole, and simile. The most frequently used figurative language on BBC Learning English Storytelling is personification because figurative language is easier to describe the behavior of objects that resemble human activities. Personification contains five sentences, metaphor contains four sentences, hyperbole consists of 4 sentences, and simile contains two sentences. Further researchers should consider the differences between each type of figurative language used as a context for evaluating the topic, find figurative language on other English education websites such as VOA (Voice of America), and have background knowledge of literature, such as songs and their features.